The ancient Maya of the Belize Valley : half a century of archaeological research - Garber, James (Maya studies., 2004)
The Ancient Maya of the Belize Valley represents an attempt to present in one volume the extensive data from the diverse sites in this part of Mesoamerica, one of the richest archaeological areas in the Maya world.